Impactos da progressão continuada na educação do estado de São Paulo - Bizelli, Jose Luis [UNESP]; Cunha, Maira Darido da [UNESP]; Pereira, Carlos Eduardo Candido [UNESP] (My University, 2013)
The presented article discuss theoretical context and the practical impact reported in the bibliography about Continued Progression at São Paulo State schools. Such proceeding, oriented through Law of Basic Guidelines, LBG, from 1996, previses a restructuring in the Basic Education at the schools, primarily with respect to evaluations. Grades are replaced for cycles and reprobation only can happen if the student exceeds the limit of stated absences or for lowered acting at final of each cycle. The impact of educational public policy drafted through Continued Progression provoke transformations that need more attention, indicating a path of reflection turned to structural conditions in order that school offers the required reinforcement to students and assure quality education. It’s primordial understand, therefore, the endogenous and exogenous factors that leaded to adoption of such proceeding in the São Paulo State.

O artigo apresentado discute o contexto teórico e o impacto prático relatado na bibliografia sobre a Progressão Continuada nas escolas do Estado de São Paulo. Tal medida, orientada pela Lei de Diretrizes Básicas, LDB, de 1996, prevê uma reestruturação do Ensino Básico nas escolas, principalmente no que tange às avaliações. As séries são substituídas por ciclos e a reprovação só pode acontecer no caso de o estudante ultrapassar o limite de faltas determinado ou por baixo desempenho no fim de cada ciclo. O impacto da política pública educacional traçada através da Progressão Continuada provoca transformações que carecem de maior atenção, indicando um caminho de reflexão voltado às condições estruturais para que a escola ofereça o reforço necessário aos alunos e garanta educação de qualidade. É fundamental compreender, portanto, os fatores endógenos e exógenos que levaram a adoção da medida no Estado de São Paulo.
Impacts of the continued progression in the São Paulo state's education
Keywords: Education; Public policies; Continued progression; Educação; progressão continuada; Políticas públicas